Digital Marketing Sebagai Strategi Pengembangan Usaha Berbasis Teknologi Pada UMKM - Yuspinus Jeranding; Nuraini Asriati; Heri Jatmiko; Maria Ulfa (Teaching and Learning Journal of Mandalika (Teacher) e- ISSN 2721-9666, 2024)
This article discusses the importance of digital marketing training as a technology-based business development strategy for MSMEs. The purpose of this article is to introduce and describe digital marketing training methods that can help MSMEs utilise the potential of digital technology in their marketing and business development. The method that is used in this article is a literature review of reliable sources related to digital marketing training and MSMEs development. The results of the literature review showed that digital marketing training can provide significant benefits for MSMEs in improving their skills and knowledge in digital marketing. This article also outlines some practical steps that can be implemented in digital marketing training for MSMEs, such as identification of digital target markets, use of digital tools and platforms, and measurement and analysis of digital marketing results. The conclusion of this article is that digital marketing training can be an effective strategy in technology-based business development for MSMEs, helping them increase their visibility, market access, and overall profitability.